2023
DOI: 10.3389/fneur.2023.1230770
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of hydrokinesitherapy in patients with dystrophinopathy

Abstract: Duchenne muscular dystrophy (DMD) is one of the most common forms of hereditary muscular dystrophies in childhood and is characterized by steady progression and early disability. It is known that physical therapy can slow down the rate of progression of the disease. According to global recommendations, pool exercises, along with stretching, are preferable for children with DMD, as these types of activities have a balanced effect on skeletal muscles and allow simultaneous breathing exercises. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, the heterogeneity of muscle involvement in the different study groups suggests that muscle-wise segmentation is necessary for detailed assessment and early disease-specific change detection, although costly and time-consuming. Future applications of qMRI could include disease monitoring, prognosis assessment, clinical trials, and treatment selections since the first applications have shown promising results [19,59,60]. As mentioned, direct comparison of qMRI study results is often restricted due to different and complex acquisition and processing pipelines.…”
Section: Discussionmentioning
confidence: 99%
“…However, the heterogeneity of muscle involvement in the different study groups suggests that muscle-wise segmentation is necessary for detailed assessment and early disease-specific change detection, although costly and time-consuming. Future applications of qMRI could include disease monitoring, prognosis assessment, clinical trials, and treatment selections since the first applications have shown promising results [19,59,60]. As mentioned, direct comparison of qMRI study results is often restricted due to different and complex acquisition and processing pipelines.…”
Section: Discussionmentioning
confidence: 99%